2016
DOI: 10.1080/15513815.2016.1179822
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Laboratory, and Placental Findings in Perinatal Listeriosis

Abstract: Clinical, laboratory, and placental manifestations of perinatal listeriosis are highly variable. Herein, we retrospectively analyzed all patients treated for neonatal listeriosis at the Charité University Medical Center in Berlin, Germany, 1999-2013. A total of 16 cases were identified. In 14 patients listeriosis was confirmed in neonatal specimens, while in two only the placenta tested positive. Elevated C-reactive protein and/or interleukin-6 levels were only inconsistently found, while a marked white blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…The reasons for the age-dependent susceptibility are not entirely clear but may reflect low colonization resistance, an impaired epithelial barrier or an immature immune system 29 . Lm belongs to the major causative agents of neonatal sepsis and meningitis and is characterized by a high mortality rate of up to 30% 3 , 6 , 30 . Although the risks associated with Lm -induced CNS infection have long been established, our knowledge about the underlying mechanisms is still incomplete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the age-dependent susceptibility are not entirely clear but may reflect low colonization resistance, an impaired epithelial barrier or an immature immune system 29 . Lm belongs to the major causative agents of neonatal sepsis and meningitis and is characterized by a high mortality rate of up to 30% 3 , 6 , 30 . Although the risks associated with Lm -induced CNS infection have long been established, our knowledge about the underlying mechanisms is still incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Infections of newborns with Lm , referred to as neonatal listeriosis, are subdivided in an early-onset disease (EOD) and a late-onset (LOD) form. EOD manifests within the first days of life and is most likely acquired prenatally by aspiration of contaminated amniotic fluid 4 6 . In contrast, LOD develops several days after birth and is thought to be transmitted during parturition through contact with the maternal vaginal or intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Listeriosis is more prevalent and severe in pregnant women than in the general population, which can be attributed to pregnancy-induced maternal T-cell suppression and the ability of Listeria , with its various virulence factors, to facilitate entry into host cells and escape intracellular degradation by the host immune system. The placenta plays a role in protecting the fetus from external stimulation, but once bacteria have invaded the intervillous space, it may become a nidus for the repeated shedding of the bacteria to the mother and fetus, leading to recurrent infections [ 1 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The culture of sterile samples, such as the blood and cerebrospinal fluid, but not of the stool due to its low sensitivity, is effective only for febrile and symptomatic patients because the infected dosage determines the positive predictive rate and duration of the culture result [ 9 10 ]. Microbiological diagnosis may lead to disparity in the detection rate, due to the unavailability of Listeria -specific agar in most clinical laboratories and the difficulty of the Listeria culture, which requires microaerophilic conditions or a relatively low temperature for proliferation [ 9 10 11 ]. A prospective study reported that the placental culture was the most sensitive among the various sample cultures and other tests for maternal-neonatal listeriosis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spośród leków rekomendowanych należy wymienić antybiotyki beta--laktamowe w monoterapii lub w skojarzeniu z aminoglikozydem. Cefalosporyny nie są stosowane ze względu na naturalną odporność listerii na tę grupę antybiotyków [1,5,10].…”
Section: Wstępunclassified